Multivariate water quality analysis of selected river basins in Malaysia - Syahril Hirman Azmee
Freshwater system is crucial to life but its resources are finite. Generally, it covers only 3% of all water on the Earth. Since the vital resources are limited, the water quality of seven (7) river basins surround Malaysia was studied. The main purposes of this study were to define the possible sources of pollutants for each river basin according to their surrounding activities as well as to predefine the multivariate water quality standard which fit according to the different land use surround. Secondary water quality data was provided by the Malaysian Department of Environment (DOE). The dataset was consisted of 30 water quality parameters with up to 14 years of monitoring period. In general, based on principal component analysis (PCA), the main possible sources of pollutants that contributed towards the declining of selected Malaysian river water quality are, the surface run-off with high loaded soil and dissolution of earth mineral primarily the limestone towards the water column. A part from that other factors that likely deteriorating the particular water column are the anthropogenic pollutants d rived from domestic and industrial wastewater, excessive usage of organic materials in agricultural activities, organic waste dumping, inorganic waste disposal and the byproducts of sand mining activitie . The water quality index guided by DOE has emphasized only six (6) parameters are counted to define the status of water quality namely dissol ed oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), pH, suspended solid (SS) and ammoniacal-nitrogen (NH3-N. However, in the present study, the discriminant analysis (DA) has highlighted the count of significant parameters which act as pollutants towards the Malaysian river water quality are more than those six (6) parameters. A part of the significant parameters highlighted by DA are earth minerals, Escherichia-coli (E-coli), sal inity, phosphate (P04 , nitrate (N03) as well as metals. Therefore, the present study has developed a distinctive multivariate water quality index according to the land use surround for each seiect®P river basin. Apparently, comparison between DOE water quality index with the present MWQI has exhibited numerous predefined status of selected river water quality corresponding to their surround land use. Present study illustrates the utility of multi ariate analysis in order to predefine the actual water quality status of the selected Malaysian river basins for the effective freshwater quality management in future.